2009
DOI: 10.1007/s11666-009-9316-3
|View full text |Cite
|
Sign up to set email alerts
|

Two-Directional Nodal Model for Co-Condensation Growth of Multicomponent Nanoparticles in Thermal Plasma Processing

Abstract: A more precise but easy-to-use model is developed and proposed to clarify nanoparticle growth with twocomponent co-condensation in thermal plasma processing. Computations performed for the molybdenumsilicon and titanium-silicon systems demonstrate that the model quantitatively estimates both the particle size distribution and the composition distribution of the silicide nanoparticles produced through co-condensation as well as nucleation and coagulation. The model also successfully obtains information that can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…T from the kinetic theory [37]. This growth-transport model obtains the spatial distributions of the number density and mean diameter of nanoparticles with a lower computational cost than those of other models [12][13][14][15][16][17][19][20][21][22][23][24][25][26][27].…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…T from the kinetic theory [37]. This growth-transport model obtains the spatial distributions of the number density and mean diameter of nanoparticles with a lower computational cost than those of other models [12][13][14][15][16][17][19][20][21][22][23][24][25][26][27].…”
Section: Model Descriptionmentioning
confidence: 99%
“…Theoretical modeling and numerical studies are effective approaches, as demonstrated by other thermal plasma systems with nanopowder formation [12][13][14][15][16][17][18][19][20][21]. For an arc plasma process, Tashiro et al [22] conducted a numerical calculation based on an oversimplification that small particles do not collide and that only large particles collide and form agglomerates in a two-dimensional space.…”
Section: Introductionmentioning
confidence: 99%
“…Most metal vapours have high emissivity and significantly reduce the precursor evaporation efficiency [12][13][14]. Quench gas injection is perhaps the optimization parameter most thoroughly investigated, because it impacts strongly on flow fields, temperature distribution and cooling rates in the system [15][16][17][18]. The cooling rate that can be generated by the quench gas allows for the synthesis of nanoparticles with a narrow Particle Size Distribution (PSD).…”
Section: Introductionmentioning
confidence: 99%
“…Those models adopted several oversimplifications to obtain simple numerical solutions including only mean values. For more accurate and detailed numerical analysis in the growth processes of binary material nanopowders, we developed a unique model and solution algorithm [ 25 , 26 , 27 , 28 ]. That model can not only express any profile of particle size–composition distribution (PSCD) of a nanopowder even with widely ranging sizes from sub-nanometers to a few hundred nanometers, but can also simulate the entire formation process involving binary homogeneous nucleation, binary heterogeneous co-condensation, and coagulation among nanoparticles with different compositions.…”
Section: Introductionmentioning
confidence: 99%